Teachers’ pedagogical practices for including learners with Cerebral Palsy at a primary school in the Chipinge district, Zimbabwe - Erinet Mambwerere; Loveness Dube (International Journal of Studies in Inclusive Education)
The study explored the teachers’ pedagogical practices for including learners with cerebral palsy (LCP) in inclusive classrooms in the Chipinge district in Zimbabwe. It adopted a qualitative approach rooted in the interpretative research paradigm. It used a phenomenological research design to analyse data. Individual semi-structured interviews, non-participant observation of lesson delivery, and document analysis were used for data collection. Nine participants were purposively sampled. Data was analysed using interpretative phenomenological analysis. The results showed teachers' various pedagogical practices when teaching LCP. These include differentiation of time and tasks, consultation and partnership, learner-centered learning, and embracing technology. The results of positive reinforcement, teaching social skills, knowing individual learners, and creating a psycho-social environment foster the inclusion of LCP in general classrooms through enhanced respect and acceptance of all learners. Challenges, which include teacher’s lack of skills and knowledge, human and material resources, and lack of skills and knowledge, were seen to be hindering the effective inclusion of LCP. Recommendations include stakeholders pursuing rights-based inclusive education awareness and parental educational programmes and providing appropriate human and material resources.